Exploring the Therapeutic Potential of Phytochemicals in Alzheimer’s Disease: Focus on Polyphenols and Monoterpenes - Piccialli, Ilaria; Tedeschi, Valentina; Caputo, Lucia; D’Errico, Stefano; Ciccone, Roselia; De Feo, Vincenzo; Secondo, Agnese; Pannaccione, Anna (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a chronic, complex neurodegenerative disorder mainly characterized by the irreversible loss of memory and cognitive functions. Different hypotheses have been proposed thus far to explain the etiology of this devastating disorder, including those centered on the Amyloid-β (Aβ) peptide aggregation, Tau hyperphosphorylation, neuroinflammation and oxidative stress. Nonetheless, the therapeutic strategies conceived thus far to treat AD neurodegeneration have proven unsuccessful, probably due to the use of single-target drugs unable to arrest the progressive deterioration of brain functions. For this reason, the theoretical description of the AD etiology has recently switched from over-emphasizing a single deleterious process to considering AD neurodegeneration as the result of different pathogenic mechanisms and their interplay. Moreover, much relevance has recently been conferred to several comorbidities inducing insulin resistance and brain energy hypometabolism, including diabetes and obesity. As consequence, much interest is currently accorded in AD treatment to a multi-target approach interfering with different pathways at the same time, and to life-style interventions aimed at preventing the modifiable risk-factors strictly associated with aging. In this context, phytochemical compounds are emerging as an enormous source to draw on in the search for multi-target agents completing or assisting the traditional pharmacological medicine. Intriguingly, many plant-derived compounds have proven their efficacy in counteracting several pathogenic processes such as the Aβ aggregation, neuroinflammation, oxidative stress and insulin resistance. Many strategies have also been conceived to overcome the limitations of some promising phytochemicals related to their poor pharmacokinetic profiles, including nanotechnology and synthetic routes. Considering the emerging therapeutic potential of natural medicine, the aim of the present review is therefore to highlight the most promising phytochemical compounds belonging to two major classes, polyphenols and monoterpenes, and to report the main findings about their mechanisms of action relating to the AD pathogenesis.